2012
DOI: 10.1007/s12011-012-9448-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Tea Supplementation on Elements, Total Antioxidants, Lipids, and Glucose Values in the Serum of Obese Patients

Abstract: The consumption of green tea has been associated with cardiovascular and metabolic diseases. There have been some studies on the influence of green tea on the mineral status of obese subjects, but they have not yielded conclusive results. The aim of the present study is to examine the effects of green tea extract on the mineral, body mass, lipid profile, glucose, and antioxidant status of obese patients. A randomized, double-blind, placebo-controlled study was conducted. Forty-six obese patients were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
170
2
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(187 citation statements)
references
References 38 publications
2
170
2
12
Order By: Relevance
“…This is consistent with data from meta-analyses (10-12), but 3 randomized, double-blind, controlled trials reported lowered concentrations of triglycerides after the consumption of GTE or beverage (30,35,44). These studies, however, were shorter in length (3 mo each) than our trial, study participants were obese, the treatment dose was much lower (EGCG doses varying from 208 to 214 mg/d), comparisons were mostly made within treatment groups, and/or the green tea supplementation was added to an exercise-induced weight-loss intervention.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with data from meta-analyses (10-12), but 3 randomized, double-blind, controlled trials reported lowered concentrations of triglycerides after the consumption of GTE or beverage (30,35,44). These studies, however, were shorter in length (3 mo each) than our trial, study participants were obese, the treatment dose was much lower (EGCG doses varying from 208 to 214 mg/d), comparisons were mostly made within treatment groups, and/or the green tea supplementation was added to an exercise-induced weight-loss intervention.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with the results of Haghighi et al weeks of aerobic training along with green tea consumption decreased body weight in obese and overweight women [17]. Suliburska et al (2012) noted that daily intake of 379 mg green tea for 3 months reduced BMI and waist circumference in obese individuals (23 males and 23 females aged 30-60 and BMI≤30 kg/m 2 ) [21]. Current evidences suggest that catecholamine status and growth hormone (IGF-1) levels which enhance lipolysis process, increase during exercise.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the participants at highest cardiovascular disease risk, a nonsignificant trend was observed for a positive association between tea consumption and HDL‐C concentrations, whereas no such trend was observed in the healthy participants 7, 8, 9. Trials conducted in participants with chronic conditions including obesity, hypertension, or other metabolic symptoms and durations >12 weeks reported significant increases in HDL‐C concentrations resulting from tea consumption 11, 13, 29, 30. Consistent with those data, in the current study we examined the long‐term effects of tea consumption on HDL‐C concentrations and found a more pronounced association between higher tea consumption and slower decreases in HDL‐C concentration over a 6‐year period in individuals aged ≥60 years or at elevated risk of developing metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings on the potential effects of tea on high‐density lipoprotein cholesterol (HDL‐C) are mixed. Some clinical trials reported a significant increase,10, 11, 12, 13 whereas other trials reported null effects14 on HDL‐C concentrations. Of note, no clinical trials examined the potential dose‐response effect of tea and were limited by the small sample sizes (10 to ≈200) and short intervention period (3 weeks to 3 months).…”
Section: Introductionmentioning
confidence: 99%